Involvement of Calcium and Calmodulin in NO-Alleviated Salt Stress in Tomato Seedlings - Nana Qi; Ni Wang; Xuemei Hou; Yihua Li; Weibiao Liao (Plants, 2022)
Salt stress is an adverse impact on the growth and development of plants, leading to yield losses in crops. It has been suggested that nitric oxide (NO) and calcium ion (Ca2+) act as critical signals in regulating plant growth. However, their crosstalk remains unclear under stress condition. In this study, we demonstrate that NO and Ca2+ play positive roles in the growth of tomato (Lycopersicum esculentum) seedlings under salt stress. Our data show that Ca2+ channel inhibitor lanthanum chloride (LaCl3), Ca2+ chelator ethylene glycol-bis (2-aminoethylether)-N,N,N,N-tetraacetic acid (EGTA), or calmodulin (CaM) antagonist N-(6-aminohexyl)-5-chloro-1-naphthalenesulfona-mide hydrochloride (W-7) significantly reversed the effect of NO-promoted the growth of tomato seedlings under salt stress. We further show that NO and Ca2+ significantly decreased reactive oxygen accumulation, increased proline content, and increased the activity of antioxidant enzymes, as well as increased expression of antioxidant enzymes related genes. However, LaCl3, EGTA, and W-7 prevented the positive roles of NO. In addition, the activity of downstream target enzymes related to Ca2+/CaM was increased by NO under salt stress, while LaCl3, EGTA, and W-7 reversed this enhancement. Taken together, these results demonstrate that Ca2+/CaM might be involved in NO-alleviate salt stress.